Priorities for research on environment, climate and health, a European perspective - Elina Drakvik; Manolis Kogevinas; Åke Bergman; Anais Devouge; Robert Barouki; on behalf of the HERA (Health and Environment Research Agenda) (BMC, 2022)
Abstract Climate change, urbanisation, chemical pollution and disruption of ecosystems, including biodiversity loss, affect our health and wellbeing. Research is crucial to be able to respond to the current and future challenges that are often complex and interconnected by nature. The HERA Agenda, summarised in this commentary, identifies six thematic research goals in the environment, climate and health fields. These include research to 1) reduce the effects of climate change and biodiversity loss on health and environment, 2) promote healthy lives in cities and communities, 3) eliminate harmful chemical exposures, 4) improve health impact assessment and implementation research, 5) develop infrastructures, technologies and human resources and 6) promote research on transformational change towards sustainability. Numerous specific recommendations for research topics, i.e., specific research goals, are presented under each major research goal. Several methods were used to define the priorities, including web-based surveys targeting researchers and stakeholder groups as well as a series of online and face-to-face workshops, involving hundreds of researchers and other stakeholders. The results call for an unprecedented effort to support a better understanding of the causes, interlinkages and impacts of environmental stressors on health and the environment. This will require breakdown of silos within policies, research, actors as well as in our institutional arrangements in order to enable more holistic approaches and solutions to emerge. The HERA project has developed a unique and exciting opportunity in Europe to consensuate priorities in research and strengthen research that has direct societal impact.